KONTRIBUSI ENERGI SOFT DRINK TERHADAP KONSUMSI ENERGI DAN STATUS GIZI SISWA SMP NEGERI 3 SUKAWATI - Kadek Mely Purwanti; I Made Purnadhibrata; I Putu Suiraoka (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
In a community a soft drink has become a daily drink, especially among adolescents and children are now consuming carbonated drinks. These lifestyle changes result in changes in diet that refer to high-calorie diets, especially soft drinks which have an impact on increasing obesity. The general objective of this study was to determine the Soft Drink Energy Contribution to Energy Consumption and Nutritional Status of Students in SMP Negeri 3 Sukawati. This type of research is observational type research with cross sectional approach. The population in this study was 83 students. While the sample of part of the population with criteria, class VII and VIII at SMP Negeri 3 Sukawati who are registered as students and class VII and VIII students in the 2019/2020 academic year who are active in attending lessons at SMP Negeri 3 Sukawati, were present at the time of research and were willing to be a sample by filling out informed consent (a statement is willing to be a sample). Based on the calculation of the sample formula in this study there were 35 people. The results in this study are the contribution to energy consumption by 11.50% while soft drink energy consumption based on nutritional status in the high categories of obesity (42.9%) and over nutrition (22.2%) compared to good nutritional status (0%).Keywords: Soft Drinks, Teenagers, Obesity